(untitled) (Calidad, Tecnología y Desarrollo Agroindustrial, 2017)
The mammon fruit (Melicoccusbijuga L.) to the sapindaceae family, is a tropical fruit native of South America and is widely scattered in Venezuela. The goal of the present project is to determine the elements contents of the fruit (the pulp or edible part of the fruit). The analytical search was aimed at phosphorous (P), potassium (K), calcium (Ca), magnesium (Mg), sodium (Na), Iron (Fe), zinc (Zn), copper (cu), manganese (Mn) and chromium (Cr). The were obtained the following concentrations: P 95,7 % mg∙g-1; K 180 % mg∙g-1; Ca 32 % mg∙g-1; Mg 58.1 % mg∙g-1 ; Na 4 % mg∙g-1; Fe 2.7 % mg∙g-1; Zn 0.6 % mg∙g-1; Cu 0.2 % mg∙g-1; Mn and Cr were not found. The content of microelements in mammon pulp makes this highly nutritious tropical fruit and could be used as a nutritional supplement, making it a result of interest to commercial and industrial exploitation.